PENERAPAN METODE DRILL DALAM MENINGKATKAN HASIL BELAJAR PAI MATERI AL QURAN ADALAH PEDOMANKU PADA SISWA KELAS X IPS SMA NEGERI 2 SIGLI PIDIE TAHUN PELAJARAN 2020/2021 - Rahmiwati Rahmiwati (Jurnal Sains Riset, 2022)
This study aims to determine the application of the drill method in improving PAI learningoutcomes. Al Quran material is my guide to Class X Social Studies students at SMA Negeri 2 SigliPidie in the 2020/2021 academic year. Meanwhile, the problem formulation in this research iswhether the application of the drill method can improve PAI learning outcomes for the Qur'anicmaterial is my guide to Class X Social Studies students at SMA Negeri 2 Sigli Pidie for the2020/2021 academic year. To obtain data, the author uses to test and non-test techniques. After thedata is collected, the writer processes and analyzes the data by comparing the results ofobservations and tests in cycle I and cycle II. From the results of the study, it can be seen that theapplication of the drill method can improve learning outcomes for PAI subjects, especially theQur'anic material is my guide for class X social studies students at SMA Negeri 2 Sigli semester1 for the 2020/2021 academic year. The increase in the average value is 51 in the initial conditionsto 70.7 in the first cycle and becomes 80.5 in the second cycle. The average value of the first cycleincreased by 19.7% from the initial condition, the average value of the second cycle increased by9.8% from the first cycle. The increase in the average value of the whole was 29.5%. Masterylearning increased from the beginning of the pre-cycle to cycle 1 by 52.8% from cycle 1 to cycleincreased by 25%. While the overall learning completeness is 75.8%. At the end of the lesson,there were positive changes in the students regarding the learning outcomes of the material, theQur'an is my guide. By using the drill method, it turned out to be able to improve PAI learningoutcomes, the Koran material was my guide, and got an average score of 80.5Keywords: The drilling method, learning outcomes, and the Qur’an are my guidelines